Tracking Interpersonality in Research Article Abstract: A Diachronic Study of Dynamic Nature of Genre - Arezou Bakhtiari; Ali Akbar Khomeijani Farahani (Journal of Language and Literature, 2020)
This study reports on interpersonality in a diachronic-contrastive investigation in Research Article (RA) abstracts. The study analyzed a corpus of 180 RA abstracts from two journalsof Psychological Bulletin and Personality and Individual Differences over the last three decades. This paper uses Hylands (2005b) Stance Model of Interaction and Hyland Tses (2005) Classification of Sentences Containing Evaluative that in order to explore interpersonality. The results of this study revealed that authors of these journals adopted different stance and positioning over time in their writing. In addition, the findings of this paper did not corroborate previous research findings that RA abstracts exhibit high number of boosters. In relation to writing pedagogy, the results of this study can help the scholars to frame their papers in order to publish them in English-medium journals.